Balanced Scorecard and Training Initiative in Organization: A conceptual discussion - Azlan Ali; Segaren Arumugam; Rashidah Kamarulzaman (Research Synergy Foundation, 2022)
A balanced Scorecard (hereafter BSC) is a strategic planning tool developed by Kaplan and Norton (1996) as a response to the assumption that organizations only exist to satisfy stockholders (Kaplan and Norton, 1992). It is based on four perspectives, where each perspective represents a different set of stakeholders: Learning and Growth, Internal Business Processes; Customers; and Finance. It enables an organization to align its strategies to achieve the objective, mission, and vision of the organization. This conceptual paper aims to provide discussions on the literature related to works pertaining to the underlying theories related to management performance and the development of the Balanced Scorecard as a performance tool in both private and public organizations. This paper also focuses on a discussion on the use of BSC as a performance management tool in civil service agencies. Many of the suggested explanations for the success or failure of BSC in public sector organizations, however, are relatively unspecific because they could be implemented similarly in the private sector. There appears to be an awareness gap with regard to the factors that hinder the introduction of BSC, especially in the public sector, therefore. Intuitively, the claims on the effective rate of implementation of the BSC prompted the intention to examine the effects of training on the improving of the BSC's efficacy in the public sector.